Analisis Nilai Tambah Produk Pala Manis Hasil Usaha Wisma Bunaken Kelurahan Tona I Kecamatan Tahuna Timur Kabupaten Kepulauan Sangihe - Mare, Lisa Lestari; Mandei, Juliana Ruth; Tambas, Jane Sulinda (Sam Ratulangi University, 2023)
The aim of this study was to calculate the added value of the “sweet nutmeg” product from the business of Wisma Bunaken in Tona I Village, Tahuna Timur District, Sangihe Archipelago Regency. The research was conducted from April to June 2022. The data used are primary data and secondary data. Primary data were obtained through direct interviews with company owners using prepared questionnaires and direct observation of conditions in the field during the analysis period. Secondary data, namely data obtained from the literature and literature through documents, publications, or research results from various institutions or institutions that support and relate to the required research topic. The results showed that 1 kilogram of nutmeg flesh processed by the Sweet Nutmeg Business of Wisma Bunaken, Tona I Village, Tahuna Timur District, Sangihe Islands Regency provided an added value of IDR 54,955 with a ratio obtained of 91.59 and a contribution of 18.20 workers and a additional packaging of IDR 14,955 for 100 gram packages and IDR 34,955 for 200 gram packages with ratios obtained of 0.74 and 0.87 for 100 and 200 gram packages.